Zoneamento geoambiental da bacia hidrográfica do rio Jaguari – oeste do RS - Santos, Vinicius Silveira dos (2018)
Over the years, and the growing use of natural resources by society, studies are needed that can contribute to the proper environmental planning, so that nature is not impacted aggressively. Thus, studies are needed that can make the use of natural resources possible by the human being in an organized way, so that it does not impede the dynamics of evolution of the relief, and that the anthropic action is not decisive in the degradation of the environment. In the process of developing environmental studies, river basins begin to be the territorial unit of analysis that best represents these types of studies. Geoenvironmental zoning can be characterized as an instrument of assistance in planning and territorial planning, at a local or regional scale. The main objective of this work is to carry out the geoenvironmental zoning of the Jaguari River Basin, located in the west of Rio Grande do Sul, in order to provide information on the skills and restrictions of use, that is, to define potentialities and fragilities in the area of study. The bibliographic review presents the questions regarding the Importance of the Systemic Approach in Environmental Studies, the Hydrographic Basin as a unit of planning and management, the Use of Geoenvironmental Cartography and Geotechnology in Geoenvironmental Studies and, finally, Geoenvironmental Zoning as a contribution to environmental planning. The methodology is based on the analysis of the physical parameters of the relief, lithologies, soil types and land use and occupation, the post-processing of the data involved for the elaboration of geoenvironmental zoning. For this, at first, some results were presented referring to the physical elements of the relief, giving emphasis to the drainage network and relief parameters. In a second moment, the other parameters, such as lithology, soils, geomorphological compartmentalization and land use and occupation analysis were analyzed. Finally, the four Geoenvironmental Systems and the seven Geoenvironmental Units were defined, which contributed to the Geoenvironmental Zoning of the Jaguari River Basin.